Prediction of tool-chip contact length based on slip-line modeling of orthogonal cutting with rounded-edge cutting tools - Altan, Erhan; Kocabas, Sukru (TAYLOR & FRANCIS INC, 2024)
It is known that no cutting tool has a perfectly sharp cutting edge and that there is always a small rounding on the cutting edge of the tool. In this study, a new tool-chip contact length equation is presented for cutting tools with rounded-edge in orthogonal cutting. This equation was obtained based on a newly developed slip-line model. This newly developed slip-line model has rounded-edge cutting and considers the presence of a dead metal zone in front of the cutting edge. To verify the newly developed tool-chip contact length equation, experimental studies were conducted at various cutting speeds and uncut chip thickness values at both 0 degrees and 6 degrees rake angles, using cutting tools with 50 mu m-100 mu m-150 mu m edge radii. Orthogonal cutting experiments were carried out using the shaping-based quick stop device and brass (CuZn30) material was chosen as a workpiece that allows continuous chip formation without built-up edge. Strong correlation was observed between the experiment results and values that were obtained from the newly developed tool-chip contact length equation.
Keywords: Cutting edge radius; orthogonal cutting; slip-line model; tool-chip contact length; FIELD SOLUTIONS; WIDE-RANGE; PART I; TEMPERATURE; FRICTION; Engineering; Materials Science